Meaning and phenomenon in the phenomenological interpretation of poetic text. - medaguine, hichem (El Omda in Linguistics and Discourse Analysis, 2025)
This paper aims to define the meaning from the perspective of phenomenological research, which assumes the term phenomenon as a summation of meaning and its investment through phenomenological interpretation in reading the poetic text as a new approach in reading and understanding the text through inevitable phenomenological steps, namely the intent, the phenomenological response and the transcendental ego, which are the necessary steps that must be followed Critic to reveal poetic meaning. The research has reached important results that promote the phenomenological reading of the poetic text by considering poetry as an artistic phenomenon that accepts perception and awareness from the perspective of phenomenological interpretation, which begins with intent and then bends or apocalypse and ends with the transcendent ego that concludes the final meaning of the text